A Parametric Study of Elastic Web Buckling in Steel Plate Girders with Transverse Stiffeners - Hajdo, Emina; Hadzalic, Emina; Ibrahimbegovic, Adnan (European Journal of Computational Mechanics, 2026)
This study presents a numerical investigation into the elastic buckling behaviour of steel plate girders with transverse stiffeners, focusing on the web buckling mode. The influence of key parameters, including web thickness, stiffener thickness and spacing, and flange-stiffener connectivity, is examined to understand their effect on the critical buckling load associated with this mode. Elastic buckling analyses are carried out for various combinations of these parameters using a finite element model based on a nonlinear shell element formulation, which incorporates von Kármán-type nonlinear strain-displacement relations to effectively capture geometric nonlinearities and local instability phenomena. The results are systematically presented and discussed to highlight the sensitivity of buckling performance to each parameter. Detailed insights are provided into the underlying structural behaviour, revealing trends and interactions that govern the elastic web stability of steel plate girders with transverse stiffeners across different design configurations.